Elicitation Induced α-Amyrin Synthesis in Tylophora indica In Vitro Cultures and Comparative Phytochemical Analyses of In Vivo and Micropropagated Plants - Jyoti Mamgain; Abdul Mujib; Yashika Bansal; Basit Gulzar; Nadia Zafar; Rukaya Syeed; Ali Alsughayyir; Yaser Hassan Dewir (Plants, 2023)
Tylophora indica (Burm. f.) Merrill is an endangered medicinal plant that possesses various active agents, such as tylophorinine, kaempferol, quercetin, α-amyrin and beta-sitosterol, with multiple medicinal benefits. α-amyrin, a triterpenoid, is widely known for its antimicrobial, anti-inflammatory, gastroprotective and hepatoprotective properties. In this study, we investigated the metabolite profiling of tissues and the effects of cadmium chloride and chitosan on in vitro accumulation of alkaloids in T. indica. First, the callus was induced from the leaf in 2,4-D-, NAA- and/or BAP-fortified MS medium. Subsequent shoot formation through organogenesis and in vitro roots was later induced. Gas chromatography–mass spectrometry (GC–MS)-based phytochemical profiling of methanolic extracts of in vivo and in vitro regenerated plants was conducted, revealing the presence of the important phytocompounds α-amyrin, lupeol, beta-sitosterol, septicine, tocopherol and several others. Different in vitro grown tissues, like callus, leaf and root, were elicited with cadmium chloride (0.1–0.4 mg L−1) and chitosan (1–50 mg L−1) to evaluate the effect of elicitation on α-amyrin accumulation, measured with high-performance thin layer chromatography (HPTLC). CdCl2 and chitosan showed improved sugar (17.24 and 15.04 mg g−1 FW, respectively), protein (10.76 and 9.99 mg g−1 FW, respectively) and proline (7.46 and 7.12 mg g−1 FW), especially at T3 (0.3 and 25 mg L−1), in the leaf as compared to those of the control and other tissues. The antioxidant enzyme activities were also evaluated under an elicitated stress situation, wherein catalase (CAT), superoxide dismutase (SOD) and ascorbate peroxidase (APX) displayed the highest activities in the leaf at T4 of both of the two elicitors. The α-amyrin yield was quantified with HPTLC in all tested tissues (leaf, callus and root) and had an Rf = 0.62 at 510 nm wavelength. Among all the concentrations tested, the T3 treatment (0.3 mg L−1 of cadmium chloride and 25 mg L−1 of chitosan) had the best influence on accumulation, irrespective of the tissues, with the maximum being in the leaf (2.72 and 2.64 μg g−1 DW, respectively), followed by the callus and root. Therefore, these results suggest future opportunities of elicitors in scaling up the production of important secondary metabolites to meet the requirements of the pharmaceutical industry.